Beda Pengaruh Penambahan Latihan Resisted dan Hold Relax terhadap Nyeri pada Osteoarthritis Lutut - Sidiq, Fajar Mochammad, Maskun Pudjianto, SMPh., S.Pd., M.Kes (2017)
Background : Osteoarthritis is a joint disease cronic that is marked with the setback of cartilage joint and the shouider blades, it comes of new bone formation and soft tissue in and around joints are concertned. Osteoarthritis it happened because the process of the joints repair are not able to offset the damage that occurs. One of the symptoms is sore knee interfence of physiotherapy that is often used is the exercise of isotonic and isometric, the isotonic use drills resisted training while the isometric training use the hold relax. Purpose : To determine the influence of resisted exercise and hold relax against the pain of osteoarthritis knee. Benefit of Research : Knowing the influence of the provision of resisted training and hold realax on pain of the knee osteoarthritis. Knowing the influence of the effectiveness of the provision of resisted training and hold relax against the pain of osteoarthritis. Research Method : This type of research is quasi of this experiment, with the design of two group pretest-posttest design. The number of samples in this research is 16 samples, sample given resisted treatment for group I and hold relax for group II, which is conducted for three weeks with the frequency of two times a week. Statistical analiysis using wilchoxon test to the test for the influence and the Mann-Whitney test to test difference of measuring to using VAS to check how much the pain. Results : Based on the Wilcoxon statistic to the influences of the resisted with a value of 0,011<0,05 and the influence of the hold relax with a value of 0,011<0,05. While on the Mann-Whitney get results that there's a differences between resisted and hold relax, where signification 0,039<0,05. From the examination of the scale of pain the hold relax more effective because it has difference 1,225 while the resisted group have a difference. Conclusion : The influence of the provision of resisted training and hold relax to reduce the pain of osteoarthritis knee and make a difference of between exercise resisted and hold relax, and hold relax exercise is better than resisted training to decline the pain of osteoarthritis knee. Keywords : Resisted exercise. Hold relax exercise. Pain. Osteoarthritis.